A proposed mapping architecture between IAX and jingle protocols - Haj Aliwi, Hadeel Saleh; Sumari, Putra (Society of Polish Mechanical Engineers and Technicians, 2016)
Nowadays, multimedia communication has improved rapidly to allow people to communicate via the Internet. However, Internet users cannot communicate with each other unless they use the same chatting applications since each chatting application uses a certain signaling protocol to make the media call. The mapping architecture is a very critical issue since it solves the communication problems between any two protocols, as well as it enables people around the world to make a voice/video call even if they use different chatting applications. Providing the interoperability between different signaling protocols and multimedia applications takes the advantages of more than one protocol. Many mapping architectures have been proposed to ease exchanging the media between at least two users without facing any difficulties such as SIP-Jingle, IAX-RSW, H.323-MGCP, etc. However, the design of any of the existing mapping architectures has some weaknesses related to larger delay, time consuming, and security matters. The only way to overcome these problems is to propose an efficient mapping architecture. This paper proposed a new mapping architecture between Inter-Asterisk eXchange Protocol and Jingle Protocol. The proposed mapping architecture consists of IAX domain (IAX client, IAX server, IAX-to-Jingle gateway), and Jingle domain (Jingle client, Jingle server, Jingle-to-IAX gateway). The tasks of the translation gateways are represented by the URI conversion, media capability exchange, translator of call setup and teardown signals, and real time media transmission.